2005
DOI: 10.1152/ajpgi.00227.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of microtubules in estradiol-17β-d-glucuronide-induced alteration of canalicular Mrp2 localization and activity

Abstract: (E2-17G) induces a marked but reversible inhibition of bile flow in the rat together with endocytic retrieval of multidrug resistance-associated protein 2 (Mrp2) from the canalicular membrane to intracellular structures. We analyzed the effect of pretreatment (100 min) with the microtubule inhibitor colchicine or lumicholchicine, its inactive isomer (1 mol/kg iv), on changes in bile flow and localization and function of Mrp2 induced by E2-17G (15 mol/kg iv). Bile flow and biliary excretion of bilirubin, an end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 45 publications
9
54
0
Order By: Relevance
“…Mrp2, as well as Bsep and Mdr1, have all been identified in intracellular vesicular structures in addition to the canalicular membrane in rat liver 20,21 . Furthermore, Mrp2 and Bsep are regulated rapidly by retrieval from and/or insertion into the canalicular membrane via intracellular vesicles 21,22,23,24,25 . In support of our finding, a recent study in WIF-B9 cells colocalized apical ABC transporters and Rab11 in polarized cells and restricted these transporters to Rab11-endosomes in non-polarized cells where no canalicular pole was formed 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Mrp2, as well as Bsep and Mdr1, have all been identified in intracellular vesicular structures in addition to the canalicular membrane in rat liver 20,21 . Furthermore, Mrp2 and Bsep are regulated rapidly by retrieval from and/or insertion into the canalicular membrane via intracellular vesicles 21,22,23,24,25 . In support of our finding, a recent study in WIF-B9 cells colocalized apical ABC transporters and Rab11 in polarized cells and restricted these transporters to Rab11-endosomes in non-polarized cells where no canalicular pole was formed 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Blocking of biliary transport by way of altered localization of efflux drug transporters could, in conjunction with increased expression of Abcc3 on the sinusoidal membrane, drive the shift from biliary to plasma efflux. Likewise, Mottino et al (2002Mottino et al ( , 2005 have shown that altered localization of Abcc2 during estradiol-17␤-glucuronide-induced cholestasis results in reduction of the biliary concentration of Abcc2 substrates. Zhang et al (2005) observed a similar phenomenon in sandwich-cultured rat hepatocytes.…”
Section: Ezetimibe Disposition Is Altered In Experimental Nashmentioning
confidence: 99%
“…Our group has recently demonstrated that GPR30, a GPCR, and ERα accounts in part for the acute cholestasis caused by E17G Barosso et al 2012), event that correlates well with its ability to induce endocytic internalization of the canalicular transporters such as Abcc2 (Mottino et al 2003(Mottino et al , 2005. The actions of GPR30 and ERα in E17G-induced cholestasis constitute two independent pathways.…”
Section: Discussionmentioning
confidence: 90%
“…Cells were examined with a Nikon C1 Plus confocal laser scanning microscope, attached to a Nikon TE-2000 inverted microscope. Densitometric analysis of images was made along a line perpendicular to the canalicular vacuole using the Image J 1.44p software (Improvision, Coventry, NIH), as previously described for liver tissue slices (Mottino et al 2005). Each measurement was normalized to the sum of all intensities of the respective measurement.…”
Section: Assessment Of Abcc2 Secretory Function and Localization In Irhcmentioning
confidence: 99%
See 1 more Smart Citation